DESCRIPTION OF KNOWLEDGE, ATTITUDES, AND ACTIONS OF MOTHERS TOWARDS THE PREVENTION OF ISPA IN TODDLERS AT BINONG URBAN VILLAGE, TANGERANG - Thassya Yolanda, Ignatia; Lydia Putri Septiandani; Maria Nespita Sirait; Deborah Siregar (Antis-Publisher, 2024)
Upper Respiratory Tract Infections (URTIs) are diseases that affect the upper respiratory tract, causing death and decreased quality of life for children under five. The incidence of ARI is about 3-5 times / child / year. The incidence of ARI in Indonesia is still relatively high and has increased in 2015 by 63.45% and in 2017 Tangerang district obtained 48.56%. The cause is the lack of maternal knowledge about ARI, the attitude of parents who take it lightly because it is considered harmless, and the absence of ARI prevention measures in toddlers. Research Objective: To analyze the description of knowledge, attitudes, and actions of mothers towards ARI prevention in toddlers in Binong village. Research Methods: quantitative, with a cross sectional design. The sample size was 50 respondents who had toddlers with Accidental Sampling technique. The research instrument used a questionnaire in the form of google form. Data analysis using univariate analysis. Results: The study showed 74% lack of knowledge, 100% positive attitude, and 84% good action towards ARI prevention in toddlers owned by mothers aged 26-45 years and high school-Higher Education. Recommendation: For future researchers, it is advisable to look for factors that influence the incidence of ARI in toddlers.